Metals in the shell of Bathymodiolus azoricus from a hydrothermal vent site on the Mid-Atlantic Ridge - Cravo, Alexandra (2020)
Specimens of the mussel Bathymodiolus azoricus were collected from Menez Gwen, a relatively shallow (850 m) hydrothermal vent field on the Mid-Atlantic Ridge. Each bivalve shell (n = 21) was individually cleaned by selective chemical. The residual crystal matrix of each shell was individually analysed for the concentrations of the minor elements magnesium and strontium and the trace elements iron, manganese, copper and zinc. The chemical composition of the crystal matrix is unusual. B. azoricus is identified as a species having one of the most strontium impoverished shells amongst the marine molluscs. For a bimineral species the magnesium concentration is also extraordinary low. Despite originating from a trace metal rich environment; the metal concentrations in the shells were exceptionally low. Mean concentrations of iron, manganese, copper and zinc were 20.6, 3.7, 0.6 and 9.4 microg g(-1) respectively. Minor and trace element concentrations exhibited a marked intra-population variability. Copper concentrations increased and iron and zinc concentrations decreased with increasing shell weight. Due to its insensitivity to the high environmental levels of trace elements and the variability in intra-population concentrations induced by shell weight the crystal matrix of the shell of B. azoricus has little potential for use in environmental trace metal monitoring in areas contiguous to deep-sea hydrothermal vents.